Pengaruh Penggunaan Media Audiovisual dan Minat Belajar Siswa terhadap Pembelajaran Menulis Puisi pada Siswa Kelas X SMK Negeri di Kabupaten Karawang - Dwi Marta Gumilar; E. Zaenal Arifin; Mamik Suendarti (Universitas Indraprasta PGRI, 2021)
This study aims to determine (1) the effect of using audio visual media and learning interest jointly towards students’ ability in writing poetry (2) The effect of using audio visual media towards students’ ability in writing poetry (3) The influence of students' learning interest towards students’ ability in writing poetry. The research was conducted using a survey method. The population in this study were students from 10th grade of Vocational High School in Karawang Regency with a sample size of 88 students. The sampling technique used was multistage random sampling. The instruments used in the study were a questionnaire in the form of a Google Form and a writing skill test. Data analysis using multiple linear regression. The results of hypothesis testing obtained the following conclusions: (1) There is a significant effect on the use of instructional media and interest in learning jointly towards students’ ability in writing poetry. It can be proved that the Sig. 0.000 <0.05 and the calculated F value of 715.855> 3.95. (2) There is a significant effect of using audio visual media towards students’ ability in writing poetry. It can be proved that the value of Sig = 0.000 <0.05 and tobserved = 25.357> 1.987. (3) There is a significant effect of students' learning interest towards students’ ability in writing poetry. It can be proved that Sig = 0.000 <0.05 and tobserved = 22,672> 1,987. The implication in this research is that the use of audio-visual media, especially documentary films, and support for learning interest are sufficient to influence the ability to write descriptive texts for the better. Keywords: Learning Media, Audio Visual Media, Learnig Interest, Indonesian Poetry Writing Lessons.